The Influence of Water Cycle Diorama as a Learning Medium on Enhancing Learning Motivation of Grade V Students at SDN 1 Keling, Jepara Regency - Handayani, Intan Oktavia; Saputra, Henry Januar; Reffiane, Fine (Indonesian Academy of Social and Religious Research (IASRR), 2024)
The water cycle learning in Grade V at SDN 1 Keling still uses conventional methods like lectures and textbooks, leading to low student motivation and engagement. Interactive media, such as Dioramas, are believed to be more effective in helping students understand abstract concepts. This study examines the use of Dioramas in water cycle lessons and their impact on student motivation. Using a quasi-experimental method with a One-Group Pretest-Posttest design, students showed a significant increase in motivation and learning outcomes after being taught with Dioramas. The findings suggest that Dioramas are effective in enhancing student motivation, and it is recommended that teachers use varied learning media consistently. Future research should explore other factors that may further boost student motivation.